(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
From the point of view of liberation philosophy expressed principally by Paolo Freire and Gustavo Gutierrez, this article examines the structure of a testimonial novel that deals with the civil war in El Salvador in the 1980’s. While the novelist means to showcase the Marxist forces as a model of solidarity with the common people, a close reading of the text reveals a pattern of elitist and paternalistic attitudes that undermine her purpose.